Expression of connective tissue growth factor in asthmatic airway smooth muscle cells - Burgess, Janette K; Johnson, Peter R A; Ge, Qi; Au, Wendy W; Poniris, Maree H; McParland, Brent E; King, Greg; Roth, Michael; Black, Judith L (American journal of respiratory and critical care medicine, 2003)
There is strong evidence to implicate transforming growth factor-beta in the remodeling that occurs in asthma, as levels are increased in bronchial lavage fluid and gene expression is increased in bronchial tissue. Transforming growth factor-beta is also known to increase the release of collagen from airway smooth muscle. Here we identify for the first time a possible mechanism for the effects of transforming growth factor-beta. Transforming growth factor-beta specifically induces mRNA and protein for connective tissue growth factor in airway smooth muscle, and moreover, we report that the connective tissue growth factor response is greater in airway smooth muscle cultured from patients with asthma compared with patients without asthma. This occurs at both the level of mRNA (37.53 +/- 11.62- and 13.59 +/- 3.12-fold increase at 24 hours compared with time 0, respectively, p < 0.02) and protein production (67.57 +/- 27.80- and 3.58 +/- 0.6-fold increase at 24 hours compared with time 0, respectively, p < 0.03). The differential connective tissue growth factor response to transforming growth factor-beta in asthmatic airway smooth muscle identifies a potential role for connective tissue growth factor in the remodeling that is characteristic of severe persistent asthma.